The enzyme toilet rim block 'pCure' does not efficiently remove drug residues in a hospital setting - exemplifying the importance of on-site implementation testing. Issue 1 (1st January 2018) - Svebrant, Sofia; Olsen, Therese; Larsson, Jim; Öhagen, Patrik; Söderström, Hanna; Järhult, Josef D.
ABSTRACT: Introduction: Negative environmental effects of active pharmaceutical ingredients (APIs) are increasingly recognized, especially concerning antibiotics, and hospitals are important point sources. "pCure" is a toilet rim block containing API-degrading enzymes; the producing company claims positive in vitro results but no implementation studies have been performed.Materials and methods: In a university hospital setting, 16 weeks were randomized to installation or no installation of pCure in all 261 toilets connected to the same cesspit where sewage water was sampled daily. Ninety-six samples were analyzed for 102 APIs using liquid chromatography/tandem mass spectrometry.Results and Discussion: Fifty-one APIs were detected with a large variation in levels but no significant differences in the initial statistical analysis. More statistical testing of API level ratios (pCure installed/not installed) yielded some cases of significant decrease. Differences were small and not consistent when comparing means and medians. We cannot exclude a small pCure effect but clearly pCure has no effect of biological importance.Conclusion: pCure is not useful to reduce drug residue discharge in a hospital setting. In a bigger perspective, our study exemplifies that products claiming to reduce an environmental problem need to be tested in on-site implementation studies by independent researchers before reaching the market.